Fig. 2 in Urinary capillariosis in a free-ranging Marsican brown bear (Ursus arctos marsicanus) ... - Mariacher, Alessia; Eleni, Claudia; Fico, Rosario; Perrucci, Stefania (Zenodo, 2018)
Fig. 2. Urinary bladder, histology. Scattered eosinophils in the submucosa. Hematoxylin-eosin, 10X. ... : Published as part of Mariacher, Alessia, Eleni, Claudia, Fico, Rosario & Perrucci, Stefania, 2018, Urinary capillariosis in a free-ranging Marsican brown bear (Ursus arctos marsicanus), pp. 429-431 in International Journal for Parasitology: Parasites and Wildlife 7 (3) on page 430, DOI: 10.1016/j.ijppaw.2018.11.002, http://zenodo.org/record/13135619 ...